Potential for post‐fire recovery of Greater Sage‐grouse habitat. Issue 11 (1st November 2019) - Riginos, Corinna; Monaco, Thomas A.; Veblen, Kari E.; Gunnell, Kevin; Thacker, Eric; Dahlgren, David; Messmer, Terry
Abstract: In the western United States, fire has become a significant concern in the management of big sagebrush ( Artemisia tridentata Nutt.) ecosystems. This is due to large‐scale increases in cover of the fire‐prone invasive annual cheatgrass ( Bromus tectorum L.) and, concurrently, concerns about declining quantity and quality of habitat for Greater Sage‐grouse ( Centrocercus urophasianus ). The prevailing paradigm is that fire results in a loss of sage‐grouse habitat on timescales relevant to conservation planning (i.e., 1–20 yr), since sagebrush cover can take many more years to recover post‐fire. However, fire can have effects that improve sage‐grouse habitat, including stimulating perennial grass and forb production. The conditions under which fire results in the permanent loss or enhancement of sage‐grouse habitat are not well understood. We used long‐term data from the Utah Division of Wildlife Resources Range Trend Project to assess short‐term (1–4 yr post‐treatment) and long‐term (6–10 yr post‐treatment) effects of fire on vegetation cover at 16 sites relative to sage‐grouse habitat vegetation guidelines. Sagebrush cover remained low post‐fire at sites considered historically unsuitable for sage‐grouse (<10% initial sagebrush cover). In contrast, at sites that had higher (>10%) pre‐fire sagebrush cover, sagebrush cover decreased to <10% in the short‐term post‐fire, but by 6–10 yr after fire, most of these sites exhibited a recovering trajectory and two sites had recovered to >10% cover. Post‐fire sagebrush cover was positively related to elevation. Across all sites, perennial grasses and forbs increased in cover to approximately meet the habitat vegetation guidelines for sage‐grouse. Cheatgrass cover did not change in response to fire, and increased perennial grass cover appears to have played an important role in suppressing cheatgrass. Our results indicate that, while fire poses a potential risk for sage‐grouse habitat loss and degradation, burned sites do not necessarily need to be considered permanently altered, especially if they are located at higher elevation, have high sagebrush cover pre‐fire, and are reseeded with perennial grasses and forbs post‐fire. However, our results confirm that fire at more degraded sites, for example, those with <10% sagebrush cover, can result in cheatgrass‐dominated landscapes and sagebrush loss at these sites should be avoided.